'On the Colonization of India' (1829): Public meetings, debates and later disputes. (October 2018) - Chaudhuri, Rosinka
This article returns to the scene of excitement that comprised the topic labelled 'On the Colonization of India' in the newspapers and journals of 1829, an area explored once before by a group of established Left historians through debates on the specific issue of the 'Bengal Renaissance' in the mid-1970s. Beginning with the misreading by these historians of particular extracts from the Bengal Hurkaru in constructing their arguments for or against the place of Rammohun Roy in the making of modern India, I nevertheless draw back here from larger abstractions of categorisation to focus tightly instead on this issue of 'colonisation' alone, exploring the arguments for and against free trade in the run up to the renewal of the East India Company (EIC)'s charter in 1833 as they unfolded in Calcutta. The objective is to delink the moment from the historical narratives of English liberalism, or free trade, or later Indian nationalism, reading the archive again to bring in local perspectives that have not been looked at so far, such as the unexpected voice of Young Bengal, speaking against colonisation, not for it, as it seems Rammohun does. As a result of concentrating on the local scene in Calcutta, a different picture emerges of the varied interests that, while never arguing against British rule, were nevertheless in conflict when taking a position for or against both the company's monopoly and the future colonisation of India.